Gentrification and Resistance: Racial Projects in the Neoliberal Order - Alvaré, Melissa Archer (Social justice, 2017)
The article focuses on a gentrification conflict in Edgewood Park, a predominantly Black working-class neighborhood of a prominent mid-Atlantic city. Topics discussed include the history of localized racial projects, how gentrification is made hegemonic, and the role of gentrification in empowering individuals to resist even in the face of seemingly insurmountable challenges.